MEDIAÇÃO EM CONFLITOS COLETIVOS DO TRABALHO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present study aims to address the importance of Mediation as a procedure for managing and resolving collective labor disputes. Access to justice is a fundamental right, it is not limited to access to the Judiciary and should serve as a tool for social organizations to boost the State in the pursuit of efficient public policies, which provide the necessary instruments for the implementation and guarantees of  Rights . In this sense, the incentive to use mediation in collective labor conflicts is not only an alternative to the Judiciary, but rather as a new way of social regulation that prioritizes the restructuring of present and future relations, observing its particularities and the construction of a culture of peace and the maintenance of these relations.